2017
DOI: 10.3892/mmr.2017.6187
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a is downregulated in human osteosarcoma stem-like cells and promotes invasion, tumorigenic ability and self-renewal capacity

Abstract: MicroRNA-34 (miR-34), in particular miR-34a, has a negative regulatory effect on osteosarcoma cell proliferation, migration and invasion. Notably, it is also a post-transcriptional regulatory factor of (sex determining region Y)-box 2 (Sox-2), which is required for osteosarcoma cell self-renewal and tumorigenesis. As a direct regulator of Sox-2, miR-34a has been hypothesized to be greatly associated with the regulation of malignancies in osteosarcoma. To investigate the role of miR-34a in the malignancies of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
(35 reference statements)
1
31
0
Order By: Relevance
“…miR-34a-5p [13] and miR-20a-5p [14] can increase the chemosensitivity of osteosarcoma cells; miR-34a inhibits tumor invasion and metastasis of osteosarcoma by affecting C-IAP2 and Bcl-2 [15]. In addition, miR-34a can also reduce the self-renewal ability, tumorigenic activity and invasive ability of cancer stem cells [16]. miRNA-218 inhibits osteosarcoma cell migration and invasion by down-regulating TIAM1, MMP2 and MMP9 [17].…”
Section: Discussionmentioning
confidence: 99%
“…miR-34a-5p [13] and miR-20a-5p [14] can increase the chemosensitivity of osteosarcoma cells; miR-34a inhibits tumor invasion and metastasis of osteosarcoma by affecting C-IAP2 and Bcl-2 [15]. In addition, miR-34a can also reduce the self-renewal ability, tumorigenic activity and invasive ability of cancer stem cells [16]. miRNA-218 inhibits osteosarcoma cell migration and invasion by down-regulating TIAM1, MMP2 and MMP9 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested miRNAs could either suppress or promote tumor initiation and progression [12][13][14]. MiR-34a, an miRNA well-studied for its association with tumorigenesis, is commonly downregulated in multiple cancers, including osteosarcoma [15], colorectal carcinoma [16], prostate cancer, [17] and liver cancer [18]. A number of reports have demonstrated that reexpression of miR-34a reduces malignancy potential in many cancer cell types [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-34a, an miRNA well-studied for its association with tumorigenesis, is commonly downregulated in multiple cancers, including osteosarcoma [15], colorectal carcinoma [16], prostate cancer, [17] and liver cancer [18]. A number of reports have demonstrated that reexpression of miR-34a reduces malignancy potential in many cancer cell types [15][16][17]. It is noteworthy that miR-34a inhibits cancer stem cells in osteosarcoma and colorectal cancer [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…miR-34a targets include transcripts coding for proteins that control cell proliferation and survival, and its expression in most normal cell types promotes growth arrest, senescence, or apoptosis [151]. While miR-34a is downregulated in many cancer types [152][153][154], we observed that miR-34a is more abundant in HTLV-1-infected cell lines and in ATLL cells compared to control CD4+ cells [136,155], and provided evidence that both p53 and NF-ÎșB promote miR-34a expression in the context of HTLV-1 infection [136]. Experiments performed using a miR-34a 'sponge' construct and a synthetic miR-34 mimic provided evidence that abundant miR-34a levels provide a survival advantage to HTLV-1-infected cells, in part by controlling the expression of the pro-apoptotic BCL2 family member Bax [136].…”
Section: Deregulation Of Mirna Expression By Tax-1 and Hbzmentioning
confidence: 99%